Enhancing Adaptive Pedagogical Content Development with ADDIE and Scrum in Hypermedia Environments - Chelliq Ikram; Erradi Mohamed; Khaldi Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article explores an innovative approach that combines the ADDIE and Scrum methodologies to develop pedagogical objects in adaptive hypermedia systems. The aim is to address the evolving needs of learners in a constantly changing learning environment. This integration provides increased flexibility, allowing for quick adjustments based on learners' requirements. It also promotes multidisciplinary collaboration, enhances pedagogical quality through regular reviews, maintains alignment with educational objectives, and ensures transparent quality management. The article presents an architecture tailored to this approach, highlighting key components to promote adaptability. It discusses future prospects for the implementation of this approach, including automation and the integration of artificial intelligence, thus opening up new possibilities for continuous improvement in adaptive education and learning.